Genetic Diversity of Gloriosa superba Mutants - S., Anandhi,; C. , Kanimozhi,; K. , Rajamani, (Research Advances and Challenges in Agricultural Sciences Vol. 8, 2024)
The mutation breeding to assess character association, direct and indirect influence of characters on seed yield in the induced mutants of Glory lily and to assess the genetic variation among mutants by ISSR profile was carried out. The analysis of variance indicated significant differences among the treatments for most of the traits. Estimates of phenotypic coefficient of variation for the selected traits in VM2 generation were in general slightly higher than the genotypic coefficient of variation indicating the influence of environmental factors on these traits. High heritability and genetic advance as per cent of mean were recorded for most of the characters under the study indicating a better scope for further selection. Differential patterns resulted in ISSR analysis indicating the polymorphism created by induced mutagenesis, creating scope for the selection of desirable mutants in G. superba.